Pemberdayaan Masyarakat melalui Edukasi dan Layanan Kesehatan Dasar di Wilayah Cianten, Kabupaten Bogor - Zeze Zakaria Hamzah; Ahmad Firdaus; Murdiana Murdiana (STIKES Columbia Asia Medan, 2026)
This community service program aimed to improve access to basic health services and increase community awareness of the importance of adopting a healthy lifestyle in the Cianten area, Bogor Regency. The method used was participatory community empowerment, implemented through several stages, including a community needs assessment, health education, and free health examinations. The program was conducted collaboratively by involving students, lecturers, health professionals, and local community members. The results showed increased community access to basic health services, health-related knowledge, and awareness of adopting healthy behaviors in daily life. In addition, the program strengthened social participation and community solidarity through active involvement in each stage of the program. The implementation of the program also benefited students, particularly by developing their managerial, leadership, communication, and social awareness skills. Students acted as agents of change who encouraged the community to become more actively involved in maintaining their health and improving their quality of life. Therefore, this community service program not only had a positive impact on improving community health and awareness but also supported the development of students’ capacities through direct experience in community empowerment.